ANALISIS PENGARUH RASIO KEUANGAN RBBR TERHADAP PERTUMBUHAN LABA BANK (STUDI KASUS PT.BANK CENTRAL ASIA (BCA), Tbk) - Hana Tamara Putri (Universitas Batanghari Jambi, 2016)
This research aims to analyze the effect of the NPL, LDR, ROA, ROE, NIM and CAR variables toward Earnings Growth. The Data was used in this research based on publicity annual report of PT. Bank BCA, Tbk got from website of Bank BCA since 2004 until 2014. During research period show as data research was normally distributed. Based on multicollinierity test, heteroscedasticity test, and autocorrelation test variable digressing of classic assumption has not founded, which indicate that the available data has fulfill the condition to use multi linier regression model. Empirical evidence show as NPL and ROA partiality have an influence toward earnings growth with significance value less than 0.05. ROE, LDR, NIM, and CAR variables have no influence toward earnings growth at significance level 5%. Prediction capability from these ten variables toward earnings growth is 46.1%, where the balance (53.9%) is affected to other factors which was not to be entered to this research model.Keywords : NPL, LDR, ROA, ROE, NIM, CAR, Earnings Growth